2008
DOI: 10.4067/s0716-078x2008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Short-term feeding response of the mussel Mytilus chilensis exposed to diets containing the toxic dinoflagellate Alexandrium catenella

Abstract: Short-term feeding response of the mussel Mytilus chilensis exposed to diets containing the toxic dinoflagellate Alexandrium catenella Respuesta alimentaria inicial del bivalvo Mytilus chilensis expuesto a dietas conteniendo el dinoflagelado tóxico Alexandrium catenella

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…100 g À1 wet weight). Navarro et al (2008) showed that in mussels Mytilus chilensis exposed to A. catenella over a relatively short time; clearance and filtration rates were reduced significantly in the first few hours of exposure, but after this period, feeding activities reached similar values to the T-iso control. Additionally, Fernandez-Reiriz et al (2008) highlighted that, despite the modification of feeding and digestive processes occurring during the first day of exposure, M. chilensis was able to develop mechanisms allowing exploitation of this toxic microalga as a food source.…”
Section: Feeding Behavior and Toxin Accumulationmentioning
confidence: 75%
“…100 g À1 wet weight). Navarro et al (2008) showed that in mussels Mytilus chilensis exposed to A. catenella over a relatively short time; clearance and filtration rates were reduced significantly in the first few hours of exposure, but after this period, feeding activities reached similar values to the T-iso control. Additionally, Fernandez-Reiriz et al (2008) highlighted that, despite the modification of feeding and digestive processes occurring during the first day of exposure, M. chilensis was able to develop mechanisms allowing exploitation of this toxic microalga as a food source.…”
Section: Feeding Behavior and Toxin Accumulationmentioning
confidence: 75%
“…Alexandrium exposure is also known to have a negative impact on filtration and ingestion in bivalves (Bardouil et al, 1993;Wildish et al, 1998;Lassus et al, 1999;Li et al, 2001;Navarro et al, 2008). Inhibition of clearance was observed as the initial feeding response of Crassostrea gigas (Thunberg, 1793) exposed to A. tamarense (Lebour, 1925) and A. fundyense (Wildish et al, 1998).…”
Section: Introductionmentioning
confidence: 91%
“…Mytilus chilensis, Chilean blue mussel, also known as "chorito" or "quilmahue", is a bivalve filter feeder mollusk of the Mytilidae family found from Arica to Cape Horn in Chile (Lancellotti & Vásquez, 2000); it lives in the hard substrates of the intertidal zone to a depth of 25 m (Krapivka et al, 2007;Navarro, Contreras, & Chaparro, 2008). It is the second most important Chilean aquaculture production after salmon.…”
Section: Introductionmentioning
confidence: 99%